Simulation of ultra-high-performance concrete mixed with hematite and barite aggregates using Monte Carlo for dry cask storage - N. M., Azreen; M. Rashid, Raizal S.; Amran, Y. H. Mugahed; Voo, Y. L.; M., Haniza; M. Hairie; Alyousef, Rayed; Alabduljabbar, Hisham (Elsevier BV, 2020)
Minerals, for instance barite and hematite, absorb -rays better than silica aggregates because of their higher density. The use of these minerals as main component in ultra-high performance concretes (UHPCs) exhibit promising results and enhances the toughness of an ideal radiation absorber for nuclear facilities. However, limited information on the influence of high-density minerals on UHPC for radiation shielding is available. In this study, two UHPC mixes with hematite and barite minerals were investigated. The hardened characteristics of each UHPC like modulus of rupture, compressive strength and tensile strength, have been investigated. In addition, measurements were carried out to measure the radiation absorption characteristics of UHPC using 137Cs (3 mCi) and 60Co (2.5 mCi) sources that discharge 1.33 MeV and 0.66 MeV photons, respectively. Simulation of radiation shielding of UHPC using Monte Carlo software for Dry Cask was performed to study the radiation absorption capability of the mixes. It is found that hematite aggregate has smaller pore diameter compared to barite aggregate; thus, it is exhibited a large surface area, causing water absorption and reduced workability. Barite UHPCs showed the lowest compression strength due to a lesser percentage of Si and Fe elements. However, all UHPCs samples achieved high compression strength (>130 MPa) at 28 days. Although barite revealed higher potential to be used as gamma-ray shield because of its higher density, however, it can be concluded that the production of UHPC with silica sand is suitable for the construction of ionizing radioactivity facilities because of the abundance and low costs of the minerals.